Design and Construction of an Instrumentation System to Capture the Response of Advanced Materials Impacted by Intense Proton Pulses - F. Carra; C. Charrondiere; M. Guinchard; O. Sacristan de Frutos (Shock and Vibration)
In recent years, significant efforts were taken at CERN and other high-energy physics laboratories to study and predict the consequences of particle beam impacts on devices such as collimators, targets, and dumps. The quasi-instantaneous beam impact raises complex dynamic phenomena which may be simulated resorting to implicit codes, for what concerns the elastic or elastoplastic solid regime. However, when the velocity of the produced stress waves surpasses the speed of sound and we enter into the shock regime, highly nonlinear numerical tools, called Hydrocodes, are usually necessary. Such codes, adopting very extensive equations of state, are also able to well reproduce events such as changes of phase, spallation, and explosion of the target. In order to derive or validate constitutive numerical models, experiments were performed in the past years at CERN HiRadMat facility. This work describes the acquisition system appositely developed for such experiments, whose main goal is to verify, mostly in real time, the response of matter when impacted by highly energetic proton beams. Specific focus is given to one of the most comprehensive testing campaigns, named “HRMT-14.” In this experiment, energy densities with peaks up to 20 kJ/cm3 were achieved on targets of different materials (metallic alloys, graphite, and diamond composites), by means of power pulses with a population up to 3 × 1013 p at 450 GeV. The acquisition relied on embarked instrumentation (strain gauges, temperature probes, and vacuum sensors) and on remote acquisition devices (laser Doppler vibrometer and high-speed camera). Several studies have been performed to verify the dynamic behaviour of the standard strain gauges and the related cabling in the chosen range of acquisition frequency (few MHz). The strain gauge measurements were complemented by velocity measurements performed using a customised long-range laser Doppler vibrometer (LDV) operating in the amplitude range of 24 m/s; the LDV, together with the high-speed video camera (HSVC), has been placed at a distance of 40 m from the target to minimize radiation damage. In addition, due to the large number of measuring points, a radiation-hard multiplexer switch has been used during the experiment: this system was designed to fulfil the multiple requirements in terms of bandwidth, contact resistances, high channel reduction, and radiation resistance. Shockwave measurements and intense proton pulse effects on the instrumentation are described, and a brief overlook of the comparison of the results of the acquisition devices with simulations, performed with the finite element tool Autodyn, is given. Generally, the main goal of such experiments is to benchmark and improve material models adopted on the tested materials in explicit simulations of particle beam impact, a design scenario in particle accelerators, performed by means of Autodyn. Simulations based on simplified strain-dependent models, such as Johnson–Cook, are run prior to the experiment. The model parameters are then updated in order to fit the experimental response, under a number of load cases to ensure repeatability of the model. This paper, on the other hand, mostly focuses on the development of the DAQ for HiRadMat experiments, and in particular for HRMT-14. Such development, together with the test design and run, as well as postmortem examination, spanned over two years, and its fundamental results, mostly in terms of dedicated instrumentation, have been used in all successive HiRadMat experiments as of 2014. This experimental method can also find applications for materials undergoing similarly high strain rates and temperature changes (up to 106 s-1 and 10.000 K, respectively), for example, in the case of experiments involving fast and intense loadings on materials and structures.